Interpretations of Hijab in the Middle East: policy discussions and social implications toward women - Abdul Razak, Rafidah; Rokis, Rohaiza; Ahmad Tajudin, Bazlin Darina (IIUM Press, International Islamic University Malaysia, 2017)
Discussions on hijab or veil in the Middle East is highly controversial and debatable even until today. Although the majority of the population in the Middle East countries are comprised of Muslims, yet the policies and laws regarding the wearing of hijab by women, vary. Except for Iran and Saudi Arabia, other Middle East countries did not set the clear rulings for hijab, in fact some governments restrict its wearing in certain occupational sectors like what had been practiced in Turkey. This article aims at examining the implications of hijab policies in the Middle East in terms of the reactions and interpretations the societies make including the Western analysts towards hijab. While the famous assumption about hijab often lies at its symbolic representation as a form of men’s oppression against women, many Muslim women in the Middle East see it as a symbol of power and freedom. In order to achieve the objective, a secondary research that involves collecting of information and data from existing resources on the topic of hijab was applied. As found, the different implementation of hijab policies in the Middle East led to various interpretations and influenced women – Muslimah or not – around the globe.